Reliability Evaluation of Cryogenic Shut-Off Valve Based on Weibull Segmented Model - Yi Lu; Jian-Ming Zheng; Ting Chen (Advances in Materials Science and Engineering)
In order to improve the prediction accuracy of cryogenic shut-off valve failures and quantitatively analyze the distribution law of cryogenic shut-off valve failures, this study establishes a solution model based on genetic algorithm and statistics of cryogenic shut-off valve operating data, which is combined with two Weibull segmented models. The research analyzed the characteristics of the failure rate curve using probability statistical mathematics methods, used the K-S test method to validate the obtained two-parameter Weibull model, and compared the fitting results with the Weibull probability plot. The results show that the genetic algorithm based on D-test has both higher accuracy of curve fitting and more accurate parameters, which overcomes the shortcomings of inaccurate fitting results of WPP graphs, and can be used as a basis for theoretical assessment of reliability levels.